MiR-302a Limits Vascular Inflammation by Suppressing Nuclear Factor-κ B Pathway in Endothelial Cells - Yuan, Jia-Ni; Hong, Yu; Ma, Zhuo-Lin; Pang, Rui-Ping; Lei, Qing-Qing; Lv, Xiao-Fei; Zhou, Jia-Guo; Huang, Hui; Zhang, Ting-Ting (Frontiers in Cell and Developmental Biology, 2021)
Inflammatory response of endotheliocytes accelerates various vascular diseases. MicroRNAs (miRNAs) participate in diverse cellular processes during inflammation. Here we reported that miR-302a is an effective suppressor for vascular inflammation in endothelial cells. Firstly, MiR-302a was found decreased obviously in both patients with vascular inflammatory disease and lipopolysaccharide (LPS)-induced mice. Genetic haploinsufficiency of miR-302 aggravated LPS-induced vascular inflammatory response in mice. Furthermore, overexpressing miR-302a with mimics attenuated vasal inflammation of mice oppositely. Moreover, overexpressed miR-302a inhibited synthesis and secretion of adhesive factor in endothelial cells, and suppressed the adhesion of endotheliocytes with monocytes. In molecular mechanism, we identified that miR-302a relieved vascular inflammation mainly by regulating nuclear factor kappa-B (NF-κB) pathway in endothelial cells. The results showed interleukin-1 receptor-associated kinase4 (IRAK4) and zinc finger protein 91 (ZFP91) were the binding targets of miR-302a. MiR-302a prevented the nuclear translocation of NF-κB by inhibiting phosphorylation of IκB kinase complex β(IKKβ) and inhibitors of κBα(IκBα) via targeting IRAK4. Meanwhile, miR-302a downregulated the expression of NF-κB via binding with ZFP91 directly. In general, our study indicated that miR-302a regulates inﬂammatory responses negatively in endotheliocytes via NF-κB pathway and may be a novel target for relieving vascular inflammation.